Management Technologies to Adapt Modern Principles of Industrial Enterprise’ Management - MISHAKOV, V. Y.; BEKETOVA, O. N.; BYKOV, V. M.; KRASNYASKAYA, O. V.; VITUSHKINA, M. G. (Journal of Advanced Research in Law and Economics, 2018)
The article considers the content of the industrial management principles at the enterprise. The main principles of the production operation of modern industrial enterprises include objectivity, consistency, and scientific validation. The authors have supplemented the existing system of principles of rational production operation by additional principles such as innovativeness, transparency, and integrity. The article reflects tendencies and problems of formation and implementation of the innovative principle in industrial management at modern enterprises of various forms of ownership and economy sectors in the Russian Federation. The authors systematize management technologies to ensure the principle of transparency of production operation, and develop the mechanism to implement the principle of integrity of modern enterprises in the Russian Federation involved in the consumer goods production through the formation of a coalition loyalty program, showing the economic efficiency of this kind of management technology for all its subjects.